Sienna the Saturday fairy - Meadows, Daisy (New York : Scholastic, 2006)
Jack Frost is going to steal the fairies' magic before the fashion show unless Rachel and Kirsty help out.
Rainbow magic ;v41.
Accelerated Reader/Renaissance Learning
Keywords: Jack Frost (Legendary character) -- Juvenile fiction; Fairies -- Juvenile fiction; Magic -- Juvenile fiction; Fashion shows -- Juvenile fiction; Tate, Kirsty (Fictitious character) -- Juvenile fiction; Walker, Rachel (Fictitious character) -- Juvenile fiction; Fantasy fiction, Juvenile